2017
DOI: 10.1016/j.radi.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Image interpretation performance: A longitudinal study from novice to professional

Abstract: Wordcount:2303 Highlights 1. Some novices appear to have inherent skills in fracture identification. 2. RadBench testing as part of the UCAS selection process provides a useful indication of future performance. 3. Increase in specificity is the primary gain of university education in increasing accuracy. 4. Radiography graduates may require further education in order to deliver reliable image interpretation decisions. Abstract 248Purpose Universities need to deliver educational programmes that create radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…A future study may benefit from a pre and post additional abdominal radiograph interpretation education arm to the study. Studies focussing on musculoskeletal PCE have demonstrated the value of the integration of education with image interpretation schemes (23)(24)(25)(26). Each study shared a common theme that education can positively influence the image interpretation skill of the participant.…”
Section: Discussionmentioning
confidence: 99%
“…A future study may benefit from a pre and post additional abdominal radiograph interpretation education arm to the study. Studies focussing on musculoskeletal PCE have demonstrated the value of the integration of education with image interpretation schemes (23)(24)(25)(26). Each study shared a common theme that education can positively influence the image interpretation skill of the participant.…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of missed and/or delayed radiological diagnoses, where in‐experienced emergency clinicians make treatment decisions based on unsupported image interpretation, potentially compromise patient safety . As such, there is an increasing weight of international evidence that advocates for radiographers to generate an opinion on pathology demonstrated on the radiographs they acquire and make that opinion available to the treating team …”
Section: Introductionmentioning
confidence: 99%
“…4 Fakat PAG değerlendirmesinde, özellikle birinci basamakta çalışan hekimlerde daha fazla bilgi ve özgüven yetersizliği söz konusudur. [5][6][7][8] PAG ve diğer grafileri değerlendirmede, radyologların diğer branş hekimlerine kıyasla anlamlı derecede daha başarılı oldukları bildirilmiştir. 9 Literatürde birinci basamak sağlık merkezlerinde çalışan hekimler ile radyologlar arası röntgen filmlerinin değerlendirilmesindeki yorum farkı %22,20 olarak belirtilmiştir.…”
Section: Introductionunclassified